An evaluation of professional development for staff working with nursing students in distress. (4th March 2022) - Ryan, Colleen; Mulvogue, Jennifer
Abstract: Clinical learning experiences are known to exacerbate nursing student anxiety, causing them to present to clinical placement in distressed, meaning anxious, states. Students already living with anxiety are also more likely to suffer setbacks at this time. Supervising Registered Nurses (RNs), in the clinical settings, struggle to support this student cohort. A professional development activity was designed to introduce RNs to higher education and nursing students' known mental health concerns (such as anxiety) and to arm them with strategies for working with distressed students. A research approach that enabled researchers to collaborate with participants was employed to design the intervention. A study evaluated the impact of the educational intervention with 45 Australian RN supervisors. Two tailed T ‐tests were chosen to explore the statistical difference between pre‐ and post‐test mean results across the survey items. A 95% confidence interval was used. Statistical significance was set at <0.05. The evaluation indicated the activity could be useful for improving supervising RNs' mental health literacy, thus enhancing their understanding of how to work with distressed students. Participants recommended the activity be offered to any staff supporting student clinical learning. Collaboration between nursing researchers and nursing clinical staff produced a meaningful professional development activity and motivated the participants to increase their mental health literacy and understanding of strategies to support distressed students. Future projects should adopt similar approaches that would support both RNs' ability to support students' during clinical learning and students in distress would also benefit.